Factor Influencing the Resurgence of Brown Planthopper in Bangladesh (SAARC Journal of Agriculture, 2020)
Possible causes of brown plant hopper resurgence were determined at the net-house of Entomology Division of Bangladesh Rice Research Institute (BRRI) during 2015. Causes of resurgence in the form of resurgence ratios were higher with acetamiprid, acephate, chlorpyrifos, cypermethrin, deltamethrin, fenvalerate, lambda cyhalothrin, thiamethoxam insecticides compared to imidacloprid, cartap, dinotefuran, isoprocarb /MIPC, phenthoate, pymetrozine when even applied at recommended dose. However, thiamethoxam, imidacloprid, isoprocarb / MIPC and cartap applied at sub-lethal dose produced higher resurgence ratio of BPH than others. Isoprocarb / MIPC, a commonly used recommended insecticide was found to have a higher resurgence ratio with the insecticide treatment at the egg stage (1.71) and combination of all stages (0.82). These insecticides influenced on the growth and reproductive physiology of rice brown planthopper and consequently resurgence ratio ranged increased.SAARC J. Agri., 18(1): 117-128 (2020)